Implementation Of Data Mining And Maching Learing In The Concept Of Cybersecurity To Overcome Cyber Attack - et. al., T. Chandrakala, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper examines a high potential routing protocol for cyber security that can be used in WSN based Internet of things applications with heavy traffic loads. DM was the most effective and evolving technologies for extracting previously unknown useful patterns and trends in order to improve an organization's efficiency. All companies are increasingly expanding with the help of data mining capabilities. Data mining aids in the discovery of previously discovered and highly profitable information in large amounts of data. The main goal of database knowledge exploration was to find novel trends in large set of data. It combines a variety of domains, including statics, artificial intelligence and machine learning. DM converts a large data collection into a logical structure and extracts significant information, allowing users to gain insight into the raw data obtained from different Internet of things applications. As a result, the Internet of Things was a network of physical things or object that is fixed with network communication, electronics and sensors to capture and share data. To start the global computation, the BS asks the Cluster heads to compute tasks like help and trust, and then the agent at every CH gives a request to its CMs to start the local computation. This reduces the size and no. of message sent from and to CMs and Cluster heads, as well as between Cluster heads and BS, reducing the amount of energy consumed and extending the network's lifetime.